Enhancing Leadership for Sustainable Digital Transformation: Insights from Secondary Schools - Esi Hairani; Alex Winarno; Deni Hermana (AL-ISHLAH: Jurnal Pendidikan, 2025)
Digital transformation in secondary education presents opportunities for innovation but also poses sustainability challenges that extend beyond technological implementation. This study explores the critical role of leadership in ensuring the sustainable integration of digital technologies in private secondary schools. A mixed-methods design was employed, involving a survey of 284 teachers from private high schools in West Java and Jakarta, alongside in-depth interviews with school leaders. Quantitative data were analyzed using Structural Equation Modeling (SEM) to examine the relationships between leadership, institutional culture, digital maturity, and transformation outcomes. Findings indicate that leadership has a significant direct and indirect impact on digital transformation. Specifically, effective leadership fosters a supportive institutional culture and enhances digital maturity, both of which are essential for schools to successfully adapt to digital change. Schools with strong leadership demonstrated higher levels of readiness and adaptability in navigating technological shifts. The study underscores leadership as a key driver in aligning institutional culture with digital infrastructure to sustain transformation efforts. A robust digital ecosystem—characterized by well-developed infrastructure, collaborative practices, and effective governance—was found to be essential for long-term success. Strategic leadership is vital for the sustainable digital transformation of educational institutions. Strengthening leadership capabilities is crucial for cultivating digital maturity and achieving enduring institutional resilience in the face of evolving technological demands.